PENGARUH MEDIA PROMOSI TERHADAP PENINGKATAN JUMLAH SANTRI BARU PP. MUKHTAR SYAFAAT TEGALSARI BANYUWANGI - Had, Abdi Fauji; Tamami, M. Khoirut (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Islamic boarding schools are places of education where almost all learning activities are filled with studying Islam, the rest is filled or interspersed with general knowledge. and usually the pesantren is led and cared for by a Kyai, or bunyai who lives or mukim together with the santri in one location. The method of data collection (research) used in writing this thesis is a quantitative research method, namely research that provides an objective picture on the basis of a problem in research. In this study, the approach used is descriptive analysis, namely describing variable by variable, through observation, documentation, and questionnaires. To test the validity of the data using Pearson's correlation, while to find the reliability of the data using corrected item-total correlation, then hypothesis testing using the product moment formula, data analysis using correlation. The population in this study were PP students. Mukhtar Syafa'at while the sample was some students who were taken randomly, totaling 50 students. After analyzing the data, it can be concluded that: (1) there is an effect of the variable influence of Promotional media (X) on the variable of increasing the number of new students (Y) (2) Promotional media has a positive and significant effect on increasing the number of new students of PP. Mukhtar Syafa'at, the effect is 49.2% while the remaining 41.8% is influenced by other (independent) variables.